Three notes on Laufer’s law - Hill, Nathan W. (2024)
Facets of both Old Tibetan and Old Burmese phonology pose problems for the generalisation, known as Laufer‘s law, that -wa- in in Written Burmese corresponds to -o- in Written Tibetan. Some Tibetan words retain the sequence -wa, appearing to contradict Laufer‘s law. Some Written Burmese words with -wa originate from Old Burmese words written with -o-. To account for these anomalies and the Chinese cognates of the lexemes involved, Laufer‘s law must be understood as the product of four separate sound changes.